A description of the second species of the genus Bleptus Eaton, 1885 (Ephemeroptera: Heptageniidae) from Japan, and phylogenetic relationships of two Bleptus mayflies inferred from mitochondrial and nuclear gene sequences - Tojo, Koji; Miyairi, Ken; Kato, Yuto; Sakano, Ayana; Suzuki, Tomoya (Zootaxa, 2021)
A new mayfly species, Bleptus michinokuensis sp. nov. (Ephemeroptera: Heptageniidae) is described on the basis of specimens of male and female adults and mature nymphs collected at a seepage zone of a small freshwater branch of the ‘Tachiya-zawa-gawa’ River located amongst the northern foothills of Mt. Gassan (Shonai-machi Town, Yamagata Prefecture, Japan). This new Bleptus species is characterized by its clear fore and hind wings. That is, they neither exhibit the distinct black band on the fore wings, nor the characteristic darkened margins along the edges of both the fore and hind wings. Rather it has a blackish colored terminal half of its fore legs (i.e., tibial, tarsal and pretarsal segments). These features differ clearly when comparing them to the other known species, Bleptus fasciatus Eaton. The information and data describing the habitat and distribution range of this new species are also noted. We also examined and discussed the genetic relationship of two Bleptus mayflies to settle the taxonomic status, inferred from the partially sequenced cytochrome c oxidase subunit I (COI) and large mitochondrial ribosomal subunit (16S rRNA) genes, and also the nuclear internal transcribed spacer 2 (ITS2) gene sequences. Consequently, phenetic and molecular phylogenetic analyses agreed well in terms of clustering.